2016
DOI: 10.1002/jssc.201600038
|View full text |Cite
|
Sign up to set email alerts
|

Determination and pharmacokinetic study of four lignans in rat plasma after oral administration of an extract of Valeriana amurensis by ultra‐high performance liquid chromatography with tandem mass spectrometry

Abstract: A selective and sensitive ultra-high performance liquid chromatography with tandem mass spectrometry method was developed and validated for the determination and pharmacokinetic study of (+)-8-hydroxypinoresinol-4'-O-β -D-glucopyranoside, prinsepiol-4-O-β-D-glucopyranoside, (+)-pinoresinol-4,4'-di-O-β-D-glucopyranoside, and (-)-massoniresinol 3α-O-β-D-glucopyranoside in rat plasma after the oral administration of a Valeriana amurensis extract. The analytes and ethyl 4-hydroxybenzoate (internal standard) were s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 18 publications
0
7
0
Order By: Relevance
“…Heparinized blood was centrifuged at 13 000 × g at 18°C for 5 min to obtain plasma. Plasma samples were then removed and stored at −80°C until analysis .…”
Section: Methodsmentioning
confidence: 99%
“…Heparinized blood was centrifuged at 13 000 × g at 18°C for 5 min to obtain plasma. Plasma samples were then removed and stored at −80°C until analysis .…”
Section: Methodsmentioning
confidence: 99%
“…The result indicated that the absorption of four triterpenoid saponins might be slow, and the minimum molecular masses of the analytes are 957.5 Da, larger than the favorable value (<500 Da). Based on the above situation, the low absorption may be due to poor membrane permeability [21,22]. The T max of the four analytes was 0.83-1.58 h and t 1/2 was 4.02-5.29 h, the above results indicated that the compounds are rapidly absorbed in rats, quickly eliminated, and unlikely to accumulate in vivo.…”
Section: Pharmacokinetic Studymentioning
confidence: 73%
“…It contains numerous components, such as monoterpenes, sesquiterpenes, iridoids, lignans, alkaloids, and flavonoids . Furthermore, V. amurensis extracts have hypnotic, antidepressive, antispasmodic, and sedative effects . UPLC‐MS–based metabolomics were performed to investigate the plasma metabolic profiles and potential biomarkers in Aβ 25–35 ‐induced AD mice after treatment with V. amurensis extracts.…”
Section: Metabolomics: a Tool For Understanding Natural Drugs Against Admentioning
confidence: 98%
“…Valeriana amurensis is a traditional medicinal plant from the Valerianaceae family that is extensively used in folk medicine for the treatment of neurasthenia and insomnia. It contains numerous components, such as monoterpenes, sesquiterpenes, iridoids, lignans, alkaloids, and flavonoids . Furthermore, V. amurensis extracts have hypnotic, antidepressive, antispasmodic, and sedative effects .…”
Section: Metabolomics: a Tool For Understanding Natural Drugs Against Admentioning
confidence: 99%
See 1 more Smart Citation